A review of the genus Pulcheria Alphéraky, 1887 with description of a new species from southeastern Kazakhstan (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Matov, Alexej Yu. (Zootaxa, 2015)
A small Central Asian genus Pulcheria Alphéraky, 1887 is revised. One new species, P. kasymkhani Volynkin & Matov, sp. n. is described from southeastern Kazakhstan (Almaty region). The lectotype for P. catomelas Alphéraky, 1887 and the neotype for P. cinescens Draudt, 1938 are designated. The adults, male and female genitalia are illustrated.